IDENTIFICATION OF CLASSES OF COMPOUNDS AND ESTIMATION OF FLAVANOID AND PHENOL FROM SEEDS OF PIPER LONGUM AND PIPER NIGRUM - PRIYA N. C; P. SARAVANA KUMARI (International Journal of Pharma and Bio Sciences, 2016)
The present investigation deals with the identification of phytochemical compounds present in chloroform and methanol extract of Piper longum and P. nigrum .It showed the presence of phytochemical constituents like tannins, terpenoids, and phenolic compounds, alkaloids and flavonoids. The total phenolic content was determined using the Foin-Ciocalteu assay and total flavonoids by the Aluminium chloride colorimetric assay. Percentage of phenol in mg equivalence of gallic acid of both the peppers in chloroform and methanol extract was same and the percentage of flavonoids in mg equivalence of Quercetine was high in both pepper species. In order to find out the chemical compounds GC-MS analysis was done. It showed the presence of 10-15 volatile compounds and it gave an integrated percentage of many compounds. The black pepper in chloroform contains 15 components, out of that highest integrated percentage of Aspartic acid were present .In the case of long pepper in chloroform extracts gave 14 components, out of that the highest integrated percentage of Micosporine and Graveoline were present. However further studies are focussed towards the importance of these compounds to prevent diseases.